RISE OF ISLAM IN KASHMIR VALLEY - Dr. Shabir Ahmad Lone; Mohammad Ishaq Lone; Dr. R. Abida Begum; Dr. Hilal Ahmad Parray (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Kashmiri Muslims are an ethnic group native to the Kashmir Valley in Indian-administered Kashmir, predominantly adhering to Sunni Islam. They refer to themselves as "Koshur" in their native language. The widespread conversion to Islam in the valley occurred primarily in the 14th century, significantly influenced by the efforts of Mir Sayyid Ali Hamadani, a Persian Sufi mystic from Hamedan, Iran, who visited Kashmir multiple times during the 1370s and 1380s. His arrival, along with his disciples, marked a turning point as many settled in the region, promoting Islamic teachings. Earlier Islamic influences date back to the 12th and 13th centuries, with figures like Bulbul Shah (Syed Sharaf-ud-Din Abdur Rahman Suhrawardi), the first Muslim missionary in Kashmir, playing a key role. Additionally, the first known Quran manuscript in Kashmir, calligraphed by Fateh Ullah Kashmiri in 1237 AD, underscores the intellectual engagement with Islam during this period. This document explores the historical dissemination of Islam in the Kashmir Valley and the enduring impact of notable Islamic scholars on the region's spiritual and cultural evolution.